THE DEVELOPMENT OF STUDENTS WORKSHEETS BASED ON SCIENTIFIC APPROACH ORIENTED TO CRITICAL THINKING SKILLS ON THEME WAVE AND DISASTER - Selvia Selvia; Mudmainah Vitasari; Liska Berlian (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
Natural disasters can negatively affect life because they cause damage. Therefore, students have to be equipped with knowledge regarding them. One way is to use a student worksheet based on a scientific approach to waves and disasters. This research aimed to measure the validity levels of the student worksheet based on the developed scientific approach. According to Thiagarajan, the research and development method with the 4D development model. However, the development stage was narrowed down by defining, designing, and developing. These steps were done because this research is limited by energy, time, and cost and focused on measuring product validity; as a result, the dissemination stage was not conducted. The instrument used in this research was validation sheets filled out by two expert lecturers and three science teachers. The research results showed that the validity level of the student worksheet based on a scientific approach oriented to critical thinking skills on wave and disaster themes obtained a percentage of 83.62%, with very valid criteria. As a result, the student worksheet based on the scientific approach of the wave and disaster theme can be tested in science learning to foster students' critical thinking skills.